Oral tolerance induction with altered forms of ovalbumin - Stransky B. (Brazilian Journal of Medical and Biological Research, 1998)
As a T cell-dependent phenomenon, oral tolerance is not expected to depend necessarily on native configuration of antigens. We investigated the induction of oral tolerance with modified ovalbumin (Ova). Oral administration of heat-denatured (HD-Ova) and cyanogen bromide-degraded ovalbumin was less effective than native Ova in inducing oral tolerance in B6D2F1 mice. HD-Ova was effective in suppressing delayed-type hypersensitivity (DTH) reactions but did not suppress specific antibody formation. Injection of Ova directly into the stomach, but not into the ileum or cecum, suppressed subsequent immunization to DTH reactions. Gavage with protease inhibitors (aprotinin or ovomucoid) before gavage with Ova was ineffective in blocking tolerance induction. Treatment with hydroxyurea to destroy cycling cells 24 h before gavage with Ova blocked oral tolerance induction and also the possibility to passively transfer tolerance to naive recipients with the serum of mice gavaged with Ova 1 h before. The implications of these findings about oral tolerance induction are discussed